Studying the interaction of PANI/EGCG in the electrochemical polymerization - Nga, Mai Thanh; Tuyên, Mai; Quế, Lê Xuân (Vietnam Journal of Chemistry, 2014)
This paper presents the third part – the interaction EGCG/PANi which was studied using CV technique during PANi electrochemical synthesis at different EGCG concentration in the electrolyte. The correlations between the couples Jpa–c, Epa–c, Qa–c were observed modified. The kinetics in the propagation of the electrochemical polymerization was studied through different reaction rates, such as vJpa = DJpa/Dc, vQa = DQ0/Dc, especially v(E,c) =D(DJ/DE)/Dc. The reaction rates depend simultaneously on two parameters such as E–CV polarization potential and c – number of CV polarization cycles, and has been mostly slowed due to the EGCG adding. EGCG decreased the porosity of the synthesized PANi, which is formed in small plates or thin disks, evidently different from well known form of about 300 nm fibers in the case without EGCG. The study also contributed to confirm the signification of the derivation for the investigation of PANi electrochemical synthesis which was presented previously in the first part.